2014
DOI: 10.1002/bsl.2100
|View full text |Cite
|
Sign up to set email alerts
|

Violent Female Youth: An Examination of Instrumental Violence, Psychopathy, and Offense Characteristics

Abstract: Female youth are a strikingly under-studied population within the accumulated forensic literature, yet they represent a significant and growing population within forensic contexts. Despite research demonstrating a relationship between the presence of psychopathic traits and instrumental violence among adult offenders, researchers have only recently begun to examine this relationship among juvenile offenders. Our investigation of this potential relationship among a large sample of female offenders (N = 145) who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a study of 87 Italian homicide offenders, while male murderers had higher Factor 2 scores, female murders scored higher on Factor 1 (Carabellese et al, 2020). Furthermore, neither Factor 1 nor Factor 2 predicted instrumental violence among 145 female violent adolescents in British Columbia (Hutton & Woodworth, 2014).…”
Section: Psychopathy Factor 1 and Factor 2 Scores And Instrumentalitymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 87 Italian homicide offenders, while male murderers had higher Factor 2 scores, female murders scored higher on Factor 1 (Carabellese et al, 2020). Furthermore, neither Factor 1 nor Factor 2 predicted instrumental violence among 145 female violent adolescents in British Columbia (Hutton & Woodworth, 2014).…”
Section: Psychopathy Factor 1 and Factor 2 Scores And Instrumentalitymentioning
confidence: 99%
“…While those with higher psychopathy were more likely to be identified as instrumental offenders than those with lower psychopathy (e.g., Cornell et al, 1996;Patrick, 2018;Raine, 1993), one meta-analysis questioned the hypothesis that psychopathy is more related to instrumental compared to reactive violence (Blais et al, 2014). Additionally, violent youths with high psychopathy scores did not use significantly more instrumental violence than their counterparts (Hutton & Woodworth, 2014). Moreover, a clear link between psychopathy and homicide offending has been a focus of studies (e.g., Fox & DeLisi, 2019;Rodre et al, 2019), and most of the homicides by psychopathic offenders were instrumental (Porter et al, 2018).…”
mentioning
confidence: 99%
“…In both studies, thrill-seeking was found to be strongly associated with violent offending in a proportion of delinquent youths, supporting the idea that the quest for excitement can be a powerful motivation for violence in some (perhaps mostly male) young offenders. In female young offenders, revenge or retribution has been reported as a major motivation for violence [ 23 ]. Interestingly, in this study revenge-motivated violence was classified as “instrumental”, in contrast to QVT where it is classed as controlled/aversive (lower right quadrant in Fig.…”
Section: Introductionmentioning
confidence: 99%